Multisensory-Based Science Instruction in Elementary Schools: A Systematic Review of Cognitive, Affective, and Psychomotor Outcomes - Damar Septian; Muh Fuad Firmansyah (https://journal.metanusantara.com/pedagogia, 2026)
This systematic review aims to analyze and synthesize empirical evidence regarding the effectiveness of multisensory-based science instruction in elementary schools across three domains of learning outcomes: cognitive (conceptual understanding, critical thinking), affective (motivation, attitudes, emotional engagement), and psychomotor (manipulative skills, sensorimotor coordination). This study employed a Systematic Literature Review (SLR) following the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) guidelines. Literature searches were conducted in the Scopus database with a publication range of 2015–2025. A total of 42 empirical research articles meeting the inclusion criteria were analyzed in this review. The analysis indicates that multisensory-based science instruction consistently yields positive impacts across all three outcome domains. In the cognitive domain, multisensory approaches enhance conceptual understanding, memory retention, and critical thinking skills through the integration of visual, auditory, and tactile-kinesthetic input. In the affective domain, multisensory instruction increases learning motivation, positive attitudes toward science, and emotional regulation. In the psychomotor domain, multisensory interventions develop manipulative skills, coordination, and proprioceptive awareness. This review also identifies various multisensory learning technologies and media implemented, including augmented reality, serious games, and haptic interfaces. Multisensory-based science instruction is an effective approach for developing students' holistic competencies in elementary schools. These findings have important implications for curriculum development, instructional design, and science education policy at the elementary level.